The Population, Energy and Environmental Program : An Initiative for Understanding and Sustainable Development in the Amazon Region - World Bank (Washington, DC, 2014)
Since 1998, the EAP Program, initially sponsored by the Latin American Energy Organization (OLADE) and the World Bank, has evolved into a response by the stakeholders of the countries which share the Sub-Andean and Amazon Basin to the challenge of developing a sustainable hydrocarbon industry. This document offers a description of the origins, progress, and results that the Population, Energy and Environmental Program (EAP) has had: a united effort that the stakeholders-governments, oil industry, and indigenous people-are making to reach an understanding through the dialogue and the formulation of initiatives that encourage the integration and development of hydrocarbon projects in a way compatible with the sustainable development of the Amazon region.